Human brain activity and functional connectivity associated with verbal long-term memory consolidation across 1 month - Tallman, Catherine W.; Luo, Zhishang; Smith, Christine N. (Frontiers in Human Neuroscience, 2024)
Declarative memories are initially dependent on the hippocampus and become stabilized through the neural reorganization of connections between the medial temporal lobe and cortex. The exact time-course of these neural changes is not well established, although time-dependent changes in retrieval-related brain function can be detected across relatively short time periods in humans (e.g., hours to months). In a study involving older adults with normal cognition (N=24), we investigated changes in brain activity and functional connectivity associated with the long-term memory consolidation of verbal material over one month. Participants studied fact-like, three-word sentences at 1-month, 1-week, 1-day, and 1-hour intervals before a recognition memory test inside an MRI scanner. Old/new recognition judgments with confidence ratings and response times were recorded. We examined whole-brain changes in retrieval-related brain activity and functional connectivity of the hippocampus and ventromedial prefrontal cortex (vmPFC) as memories aged from 1 hour to 1 month. Secondary analyses ensured that retrieval-related activity was not confounded by other factors affected by memory age (i.e., changes in confidence and response time or re-encoding of targets). Memory accuracy, confidence ratings, and response times changed with memory age. A memory age network was identified where retrieval-related brain activity in cortical regions increased or decreased as a function of memory age. Hippocampal brain activity decreased as memories age within an anatomical region of interest. Importantly, these changes in retrieval-related activity were not confounded with changes in activity related to concomitant changes in behavior or encoding. Exploratory analyses of vmPFC functional connectivity as a function of memory age revealed increased connectivity with the posterior parietal cortex, as well as with the vmPFC itself. In contrast, hippocampal functional connectivity with the vmPFC and orbitofrontal cortex decreased with memory age. The observed changes in retrieval-related brain activity and functional connectivity align with the predictions of standard systems consolidation theory. These results suggest that processes consistent with long-term memory consolidation can be identified over short time frames using fMRI, particularly for verbal material.